Vitamin D concentration in the blood of women with twin pregnancies and in the umbilical cord blood of newborns in relation to environmental factors - Wierzejska, Regina Ewa; Szymusik, Iwona; Bomba-Opoń, Dorota; Rzucidło-Szymańska, Iga; Wojda, Barbara; Biskupski-Brawura-Samaha, Robert (Frontiers in Nutrition, 2024)
Background: There is a huge gap in the knowledge of the body's nutrient resources in women with multiple gestations. Due to the increased demand hypothesis and taking into account common vitamin D deficits in women with singleton pregnancies, this issue should also be investigated in twin pregnancies. This study evaluated blood vitamin D concentration in women with twin pregnancies and in the umbilical cord blood of their newborns as well as analyzed environmental factors that may affect the level of this nutrient.The study included 56 women with twin pregnancies. Venous blood samples were collected from the women before delivery and umbilical cord blood at delivery to determine the total 25(OH)D concentration. The women were interviewed by a dietitian to collect data on their diet and lifestyle.Conclusions: Only a small percentage of women with twin pregnancies presented with vitamin D deficiency, which was probably related to the widespread supplementation of this nutrient. It can therefore be assumed that a dose of 2000 IU vitamin D currently recommended for pregnant women may also be appropriate for twin gestations, although further research is required to validate this finding.